Intellectual Property and Traditional Knowledge: Balancing Cultural Rights and Legal Certainty in Indonesia and Georgia - Putu Dea Ranudhara Ratnanggana; Anak Agung Ayu Ngurah Sri Rahayu; I Gede Agus Kurniawan; Maia Kapanadze (FASYA Press, 2025)
The development of the global intellectual property law system has created new challenges for the protection of traditional knowledge traditionally safeguarded by indigenous communities. Traditional knowledge, encompassing cultural expressions, medicinal practices, and environmental knowledge, often does not conform to the fundamental principles of new, individualistic, innovation-based intellectual property regimes. In this context, a crucial issue arises: how to ensure the respect of the cultural rights of traditional communities without sacrificing legal certainty in the application of modern intellectual property rules. This paper aims to analyze and compare the legal approaches of Indonesia and Georgia in protecting traditional knowledge under the intellectual property framework. The primary focus is on the balance between recognizing the collective rights of indigenous communities and the need for a secure and enforceable legal system. This research employs a normative-comparative approach, examining national legal instruments, government policies, and relevant international guidelines, including provisions from the World Intellectual Property Organization (WIPO) and the Convention on Biological Diversity. The analysis shows that both Indonesia and Georgia face similar challenges in integrating cultural values ​​into their legal systems. Indonesia has developed a community-based protection framework through the recognition of communal rights to traditional knowledge and cultural expressions. Georgia, meanwhile, places greater emphasis on a formal legal approach with the registration and documentation of traditional knowledge. This study concludes that a hybrid model combining formal legal protection and community-based mechanisms is necessary to achieve a balance between cultural rights and legal certainty